MONITORI APPLICATION DESIGN BY USING VBA AS A TOOL TO DETERMINE WASTE BANK ADAPTABILITY - Wiraatmaja, Cosmas Andi; Kristina, Helena J; Ishak, Ishak (J@ti Undip : Jurnal Teknik Industri, 2016)
Waste banks are really important for Indonesian Government as they help the country to deal with household waste issues. And to make sure that the waste banks will continue to exist, the government has done some monitoring regarding its adaptability. Even so, the monitoring they had done wasnâ€™t comprehensive enough, as it is difficult to do so. The difficulty remains on the rather complex calculation needed, which can be really tedious at times, so it deemed as time consuming and not worth the time. Monitori is designed to overcome this problem, to help the user determine the adaptability value of a waste bank. Using Microsoft Excel and its Visual Basic for Application function to design it, the application is able to do all the calculation automatically, and by doing so eliminate the calculation error possibility. The application also has some preventive measure to prevent error in the data inputting process. Monitori also designed to be flexible, so it can be used on any waste bank.Â Â